Penyuluhan Pentingnya Legalisasi Perkawinan - Setiawati Setiawati (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pamulang, 2019)
Marriage is a bond born of inner between a man and woman as husband and wife with the aim of forming a family or household that sakinah happy and remain upon the divinity of the one true God. The recording of the marriage arranged for without recording, a marriage does not have the force of law. In fact the practice in public, let alone the remote logging process didaerah-daerah wedding in the document state is rarely noticed. This is because of the lack of knowledge most villagers tegal against legislation on marriage, both from the aspect of Islamic law as well as the positive aspects of the law. It is therefore deemed necessary to do the problems associated outreach. The purpose of doing this devotion to understanding memnberikan to the community related to the importance of the Kp Sasak. legalization of marriage. The methods used in the consecration is done by giving the extension. From the results of the survey and interviews conducted before the extension is still a lot of the public who do not know how important the legalization of marriage and what are the consequences arising because of the marriage not in legalization. The existence of this extension was well received by the public, they are very enthusiastic to follow this activity. After holding this extension a lot of development going on, many communities do governance documents to legalize their marriage that was previously done in the series.